Press Up Exercises as an Alternative to Conventional Therapy of Radicular Symptoms in Patients with Low Back Pain - Jan Vagner; Ingrid Palascákova Springrova; Eva Baranova; Šárka Tomková; Elena Bendikova (Central European Journal of Sport Sciences and Medicine, 2023)
The study examines whether clinical and objective improvement can be achieved in patients with LBP (low back pain) with radicular symptoms using a 6-week exercise program based on press up exercises created from ADL (activities of daily living) movement patterns. This original study involved 10 men with acute L5 / S1 disc hernia. Before starting the exercise program, patients determined the intensity of pain VAS (Visual Analogue Scale), the intensity of paraesthesias (NSIP: numerical scale of paraesthesia intensity) and the location of paraesthesias. Magnetic resonance imaging (MRI) was used to objectify the extent of the disc hernia, spinal cord compression, and pressure acting on the dural sac. Patients completed -week exercise program consisting only of press up ADL movement patterns in a closed kinematic chain. At the end of the exercise program, patients determined the outcome values of clinical symptoms and underwent control MRI within 2 weeks at the latest. At the end of the study all patients showed a statistically significant reduction in pain intensity (p = 0.005), paraesthesia (p = 0.006). The pressure on the dural sac was reduced in all patients. One of the patients had a partial reduction of intervertebral disc hernia by 35.7 %. None of the patients had a change in spinal root compression. Conventional therapy should focus on influencing clinical symptoms that appear to correlate with dural sac compression. We dare to argue that reduction of hernia disc is not a sign of primary recovery in LBP patients with acute phase radicular symptoms.